TRACTS: a program to map oligopurine.oligopyrimidine and other binary DNA tracts - Gal, Moshe (Oxford University Press, 2003)
A program to map the locations and frequencies of DNA tracts composed of only two bases (‘Binary DNA’) is described. The program, TRACTS (URL http://bioportal.weizmann.ac.il/tracts/tracts.html and/or http://bip.weizmann.ac.il/miwbin/servers/tracts) is of interest because long tracts composed of only two bases are highly over-represented in most genomes. In eukaryotes, oligopurine.oligopyrimidine tracts (‘R.Y tracts’) are found in the highest excess. In prokaryotes, W tracts predominate (A,T ‘rich’). A pre-program, ANEX, parses database annotation files of GenBank and EMBL, to produce a convenient one-line list of every gene (exon, intron) in a genome. The main unit lists and analyzes tracts of the three possible binary pairs (R.Y, K.M and S;W). As an example, the results of R.Y tract mapping of mammalian gene p53 is described.